2013
DOI: 10.1165/rcmb.2012-0231oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginger and Its Constituents on Airway Smooth Muscle Relaxation and Calcium Regulation

Abstract: The prevalence of asthma has increased in recent years, and is characterized by airway hyperresponsiveness and inflammation. Many patients report using alternative therapies to self-treat asthma symptoms as adjuncts to short-acting and long-acting b-agonists and inhaled corticosteroids (ICS). As many as 40% of patients with asthma use herbal therapies to manage asthma symptoms, often without proven efficacy or known mechanisms of action. Therefore, investigations of both the therapeutic and possible detrimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 43 publications
6
65
1
3
Order By: Relevance
“…Dixon and Santana (40) recently asked the question, "does inhibition of PKC in ASM increase airflow during asthma and COPD?" Our current data, together with our previous in vivo studies (9), argue that this is a potential signaling mechanism to explain the bronchorelaxant properties of 6-gingerol, 8-gingerol, and 6-shogaol, and may prove a yet-unrealized target for future asthma therapies. n Author disclosures are available with the text of this article at www.atsjournals.org.…”
Section: What This Means For B 2 -Ar Desensitization and Future Therasupporting
confidence: 60%
See 2 more Smart Citations
“…Dixon and Santana (40) recently asked the question, "does inhibition of PKC in ASM increase airflow during asthma and COPD?" Our current data, together with our previous in vivo studies (9), argue that this is a potential signaling mechanism to explain the bronchorelaxant properties of 6-gingerol, 8-gingerol, and 6-shogaol, and may prove a yet-unrealized target for future asthma therapies. n Author disclosures are available with the text of this article at www.atsjournals.org.…”
Section: What This Means For B 2 -Ar Desensitization and Future Therasupporting
confidence: 60%
“…Increased PKA activity due to increases in cAMP reduces intracellular calcium by phosphorylating IP 3 receptors on the sarcoplasmic reticulum of ASM cells (35). We previously showed that pretreatment with 8-gingerol or 6-shogaol attenuated G q -induced increases in intracellular calcium (9). These effects may be attributed to increases in cAMP through PDE4-inhibitory actions of these compounds, leading to increased PKA activity.…”
Section: B-agonist-induced Relaxation In the Airwaymentioning
confidence: 95%
See 1 more Smart Citation
“…Using a flexiVent (SciReq, Montreal, PQ, Canada) as previously described (18,19), anesthetized, HDM-sensitized WT mice received nebulized XHe-III-74 (25 ml, 10 mM) or vehicle (25% ethanol in PBS) via tracheostomy 10 minutes before measuring in vivo R RS during a nebulized methacholine challenge.…”
Section: In Vivo Mouse Respiratory System Resistance Testingmentioning
confidence: 99%
“…NOVEL ROLES OF AIRWAY SMOOTH MUSCLE activity, both of which may contribute to reduced IP 3 levels (310,312). In terms of CD38, several previous studies have demonstrated that inflammation can substantially increase CD38 levels and thus enhance cADPR-mediated [Ca 2ϩ ] i and contractility (101, 125, 141-144, 147, 300, 301), and more recent data show that altered CD38/cADPR signaling contributes to the asthma phenotype (141).…”
Section: L918mentioning
confidence: 99%